AGORA, a data‐ and biobank for birth defects and childhood cancer. Issue 8 (6th May 2016) - van Rooij, Iris A.L.M.; van der Zanden, Loes F.M.; Bongers, Ernie M.H.F.; Renkema, Kirsten Y.; Wijers, Charlotte H.W.; Thonissen, Michelle; Dokter, Elisabeth M.J.; Marcelis, Carlo L.M.; de Blaauw, Ivo; Wijnen, Marc H.W.A.; Hoogerbrugge, Peter M.; Bokkerink, Jos P.M.; et al.
Abstract : BACKGROUND: Research regarding the etiology of birth defects and childhood cancer is essential to develop preventive measures, but often requires large study populations. Therefore, we established the AGORA data‐ and biobank in the Netherlands. In this study, we describe its rationale, design, and ongoing data collection. METHODS: Children diagnosed with and/or treated for a structural birth defect or childhood cancer and their parents are invited to participate in the AGORA data‐ and biobank. Controls are recruited through random sampling from municipal registries. The parents receive questionnaires about demographics, family and pregnancy history, health status, prescribed medication, lifestyle, and occupational exposures before and during the index pregnancy. In addition, blood or saliva is collected from children and parents, while medical records are reviewed for diagnostic information. RESULTS: So far, we have collected data from over 6, 860 families (3, 747 birth defects, 905 childhood cancers, and 2, 208 controls). The types of birth defects vary widely and comprise malformations of the digestive, respiratory, and urogenital tracts as well as facial, cardiovascular, kidney, skeletal, and central nervous system anomalies. The most frequently occurring childhood cancer types are acute lymphatic leukemia, Hodgkin and non‐Hodgkin lymphoma, Wilms' tumor, and brain and spinal cord tumors. Our genetic and/or epidemiologic studies have been focused on hypospadias, anorectal malformations, congenital anomalies of the kidney and urinary tract (CAKUT), and orofacial clefts. CONCLUSION: The large AGORA data‐ and biobank offers great opportunities for investigating genetic and nongenetic risk factors for disorders in children and is open to collaborative initiatives. Birth Defects Research (Part A) 106:675–684, 2016. © 2016 Wiley Periodicals, Inc.